Comparative Analysis of the Calculation of Income Tax Article 21 Before and After the Implementation of Government Regulation No. 58 of 2023 at PT Bukit Asam Tbk against Potential Overpaid Taxes in December - Azzahra, Lutfiah Azizah; Yunita H, Devianti (Dinasti Publisher, 2024)
The research conducted to Comparatibve Analysis of Income Tax Article 21 Calculations Before and After the Implementation of Government Regulation No. 58 of 2023 at PT Bukit Asam Tbk. Government regulation No. 58 of 2023 is a regulation that regulates the calculation of income tax Art. 21 using the effective tax rate. The research method used in this research are using a quantitative research method processed using SPSS Version 29. This research uses a Wilcoxon Signed Rank Test with a population of all permanent employees of PT Bukit Asam Tbk who receive income from January to December 2023, totaling 1481 employees. The research results show that hat PP 58 of 2023 has a significant negative effect on PPh 21 imposed on PT Bukit Asam Tbk employees in the December tax period and there are employees who experience overpayment.